Updates in the Clinical Development of Epacadostat and Other Indoleamine 2,3-Dioxygenase 1 Inhibitors (IDO1) for Human Cancers - Komiya, Takefumi; Huang, Chao H. (Frontiers in Oncology, 2018)
Recent application of immunotherapy in clinical oncology revolutionized our management of advanced human cancers. Checkpoint inhibitors targeting CTLA4 and PD-1/PD-L1 axis are immunotherapeutic agents currently available to treat a variety of cancers. However, novel therapeutic approach is needed to further improve patient outcome with these agents. Indoleamine 2,3-dioxygenase (IDO), a rate-limiting catalytic enzyme in the metabolism of an essential amino acid tryptophan, is overexpressed in human cancer cells, suppressing effector T cell function and promoting regulatory T cells (Tregs). Overexpression of IDO is associated with poor patient survival in several types of human cancer. These findings indicate that IDO is a promising target to improve the outcome in field of Immuno-oncology. Several orally available IDO inhibitors have entered human clinical trials over the last few years without major safety concern. Although there is no objective response in single agent trials, combination regimens with PD-1 inhibitors appears to exceed the activity of PD-1 inhibitors alone. Several late phase clinical trials will soon determine role of IDO inhibitors in cancer patients, as the research continue to test more selective IDO inhibitors in humans. In this minireview, we will discuss the recent clinical development of IDO inhibitors.